Mediation impact of manufacturing strategies on external environmental factors and manufacturing performance - Risyawati, Mohamed Ismail (2014)
The growing global competition has presented firms around the world, including manufacturers in Malaysia, with unprecedented challenges to ensure survival. Such a challenging environment should propel these manufacturers to adapt certain, well-proven manufacturing strategies, such as lean manufacturing, the inclusion of manufacturing technology and the appliance of a strategic level of flexibility. With respect to Malaysia insufficient research has been done on what are the winning formulae to overcome the mounting challenges in the business environment. In this study, all three identified strategies – lean, manufacturing technology and strategic flexibility – were investigated in depth as integrated factors that could positively improve manufacturing performance. The research framework examined the impact of such an integrated and strategic approach on the performance of Malaysian manufacturers. Data was collected using survey method, through the distribution of structured questionnaires to lean manufacturers in Peninsula Malaysia. Structural equation modeling (SEM) was used to test multiple mediator models the results of which indicated that all three strategies had a significant impact and mediated the relationship between external environmental factors and manufacturing performance. The results from this study also emphasized several interesting quasi-paradoxical relationships that implied that Malaysian lean manufacturers preferred a cautious approach towards manufacturing technology implementation, preferring to incorporate technology in a more stable business environment and viewed strategic flexibility as unfavorable toward performance improvement. This study produced a strong predictive model that explained the mediation impact of manufacturing strategies on external environmental factors and manufacturing performance that would be useful to those managing such companies. The main limitation found in this research was the small number of respondents. Future research should focus on a wider dimension for performance measurement, include additional manufacturing strategies as part of the research framework and enlarge the scope of this study in order to increase the generalizability of the research outcome.